How Zima Band Communicates in the Song Generasi Rapuh to Criticize Moral Degradation - Ardianto, Veri; Yatno, Tri; Setyoko, Rahmad (Jurnal Dakwah dan Komunikasi, 2023)
This research was conducted to determine the meaning of social criticism in the lyrics of the song "Generasi Rapuh" ZIMA Band, with an analysis of Van Dijk's critical discourse. This research uses a qualitative method with Teun A. Van Dijk's Critical Discourse Analysis Theory approach which describes discourse into three dimensions, namely: the text dimension, the social cognition dimension, and the social context dimension. Data collection techniques in this research used library research and interviews. The results of research on text analysis show that the theme raised from the song "Generasi Rapuh" can be seen from the chorus or chorus about the current generation who have a weak mentality and are easily hurt, which has become a trend for many people. In social cognition, the results of researchers' interviews with songwriters regarding songwriters' anxiety regarding the problem of moral decadence that occurs in the current generation are obtained. in a social context, through the song "Generasi Rapuh" the songwriter tries to convey his criticism with social reality or facts that occur in people's lives.